(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: Due to its large geographical area, Libya has a distinct diversity of climatic, topographic, environmental, economic and social characteristics. Thus, since ancient times, it has developed different architectural styles in desert, coastal and mountainous areas, catering to the needs of the population and adapting to environmental conditions. The research problem with this paper lies in the fact that there is a huge gap between the houses in the old desert environment and the houses of the modern days, and that there is no similarity between them. The research aims to shed light on the sustainability features of traditional desert housing, in particular the city of Ghadames, in order to derive indicators of sustainability that can be applied in the design of contemporary housing in order to minimize negative impacts on the environment. The research is based on inductive and deductive approach through the study and analysis of the architectural elements of the traditional desert dwellings in Libya. Information and data have been collected through field visits to the city, the taking of photographs of city dwellings and the conduct of a surveys on some dwellings. In this paper, one of the criteria for the sustainability assessment will be the Leadership in Energy and Environmental Design (LEED) standard, and will be applied to the principles and concepts of the traditional architecture of dwellings in the desert region of Ghadames. Research results have shown that traditional desert housing design has dealt with environmental and sustainability data in a highly efficient manner. The paper further concluded that the foundations and principles of architectural sustainability were rooted and persist in traditional desert dwellings and were applied spontaneously in a comprehensive design, including sustainability of the site through the form, direction, use of local and environmentally friendly building materials, and dependence on ventilation, natural lighting, and energy and water conservation. The paper concluded with the inclusion of some recommendations that would reduce the gap between local and contemporary architecture for the design of housing in desert areas, taking into account the application of architectural sustainability concepts.